The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1653/0015-4040(2006)89[286:eopgao]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propylene Glycol Antifreeze on Captures of Mexican Fruit Flies (Diptera: Tephritidae) in Traps Baited With Biolures and Aff Lures

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A synergistic effect of propylene glycol in BioLure traps results in increased captures of Anastrepha fruit ßies (Thomas et al 2001, Hall et al 2005, Robacker and Czokajlo 2006, Robacker and Thomas 2007, Thomas 2008). The same effect was shown for nontarget attraction to methyl eugenol traps with an accumulation of dead oriental fruit ßies (Uchida et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…A synergistic effect of propylene glycol in BioLure traps results in increased captures of Anastrepha fruit ßies (Thomas et al 2001, Hall et al 2005, Robacker and Czokajlo 2006, Robacker and Thomas 2007, Thomas 2008). The same effect was shown for nontarget attraction to methyl eugenol traps with an accumulation of dead oriental fruit ßies (Uchida et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It has been known for some time that the addition of antifreeze containing propylene glycol to preserve ßies captured in traps baited with synthetic lures (Thomas 2008) actually increases the trap catch (Thomas et al 2001). Later studies by Hall et al (2005) with Caribbean fruit ßies, Anastrepha suspensa (Loew), and by Robacker and Czokajlo (2006) with Mexican fruit ßies showed that the antifreeze was not attractive by itself but synergized the attractiveness of the synthetic lure. Propylene glycol was not shown to be the synergistic component of the antifreeze in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sweet baits and antifreeze have been examined as trapping ingredients in recent years (Landolt 1995, Ni and Holbrook 2006, Robacker and Czokajlo 2006. Molasses and unÞnished palm sugar (also known as jaggery) signiÞcantly increased capture of Mocis latipes Guenee (Lepidoptera: Noctuidae) (Landolt 1995), and a 10% honey captured Ͼ70% female C. cautella moths (Ni and Holbrook 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although antifreeze was originally used in traps to preserve insects captured in the traps, Thomas et al (2001) found that addition of antifreeze in water doubled the capture of feral Mexican fruit ßy, Anastrepha ludens (Loew) (Diptera: Tephritidae). Robacker and Czokajlo (2006) reported the addition of water with propylene glycol antifreeze as the drowning agent was Ϸ2 times more attractive than the traps baited with the lures made by Advanced Pheromone Technologies, Marylhurst, OR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation